2004
DOI: 10.1300/j001v23n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Individual, Triadic, and Group Models of Supervision

Abstract: This paper presents findings from a quasi-experimental study of fifteen students enrolled in Supervision of Counselors class regarding their perception of supervisory experiences. Considered were individual, triadic, and group models of supervision as measured by the Working Alliance Inventory, Supervisory Styles Inventory, Supervisory Working Alliance Inventory, and the Supervision of Supervision Evaluation. Overall results suggest that the sample perceived the individual and triadic models more favorably tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
3
16
0
Order By: Relevance
“…In an earlier study dealing with working alliance, Newgent, Davis, and Farley (2004) noted that triadic and individual supervision were preferred to group supervision. This study, which included 15 doctoral students enrolled in a supervision course and providing supervision, indicated that supervisors viewed individual and triadic supervision as having similar effects on working alliance, supervisor leadership style, relationship dynamics, and satisfaction.…”
Section: Current Literature and Significance Of The Studymentioning
confidence: 99%
“…In an earlier study dealing with working alliance, Newgent, Davis, and Farley (2004) noted that triadic and individual supervision were preferred to group supervision. This study, which included 15 doctoral students enrolled in a supervision course and providing supervision, indicated that supervisors viewed individual and triadic supervision as having similar effects on working alliance, supervisor leadership style, relationship dynamics, and satisfaction.…”
Section: Current Literature and Significance Of The Studymentioning
confidence: 99%
“…Several studies, published and unpublished, have examined various factors related to individual, triadic, and group supervision (e.g., Bakes 2005;Newgent, Davis, & Farley 2005;Nguyen 2004). In an unpublished dissertation, Bakes focused on the working alliance between supervisors and supervisees within individual and triadic supervision.…”
Section: Contemporary Literature and Research On Triadic Supervisionmentioning
confidence: 99%
“…Results indicated that supervisees who were in triadic supervision seemed to obtain an increased understanding of the client compared to supervisees in individual supervision. Newgent et al (2005) also focused on multiple modalities of supervision including individual, triadic, and group supervision. However, the participants in that study were giving consideration to the mode of receiving supervision of their supervision, and not to their supervision of counselors.…”
Section: Contemporary Literature and Research On Triadic Supervisionmentioning
confidence: 99%
“…Conversely, triadic supervision appears less effective than individual supervision in decreasing supervisees' identification with the supervisor (Bakes, 2005). In areas such as supervisor leadership style, working alliance, interpersonal dynamics, and level of satisfaction with supervision, triadic supervision and individual supervision have been found to be comparable (Newgent, Davis, & Farley, 2005).…”
Section: A Qualitative Examination Of Supervisors' Experiences Of Thementioning
confidence: 95%